ANALISIS FAKTOR PENENTU KEPUASAN KERJA KARYAWAN DAN DAMPAKNYA TERHADAP PELAYANAN PUBLIK PADA RUMAH SAKIT DI KABUPATEN JEMBRANA - Lilyana, Ni Putu; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.10.TAHUN 2018, 2018)
Hospitals as one of the health facilities that provide health services to the community have a very strategic role in accelerating the improvement of public health status. Therefore, hospitals are required to provide quality services in accordance with established standards and can reach all levels of society.This study aims to analyze organizational culture, leadership, motivation and employee job satisfaction influence on hospital public service, and analyze employee job satisfaction can mediate between organizational culture, leadership, and motivation to public service of hospital through job satisfaction of hospital employee in Regency Jembrana, analyzed by partial least square (PLS). The location of the research was conducted in Jembrana District. The type of data used in this study is quantitative and qualitative. Sources of data used in this study is the primary data from the results of questionnaires to respondents.The result of analysis shows that organizational culture and motivation directly have a positive and significant effect on employee job satisfaction, while leadership has no significant effect to the work satisfaction of hospital employees. Leadership, motivation, and job satisfaction of employees directly have a positive and significant impact on public services, but organizational culture has no significant effect on hospital public services. Employee job satisfaction mediates significantly the influence of organizational culture and motivation on public services, but mediates insignificantly the influence of leadership on public service hospitals in Jembrana District. It is recommended that hospital management in Jembrana District need to provide leadership training.